(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of an academic of the nursing course in a private dressing clinic through an extension project made available by that institution. Methodology: this is an experience report, based on the student’s experience of nursing activities in a dressing clinic. Results and Discussion: it is evident that the nursing professional fulfills all the steps to perform the dressing procedure, in order to promote the clinical well-being of the patient. The clinic performs approximately 144 dressings monthly, resulting in 1729 dressings in 144 working days of the year. Final considerations: The study contributed to the formation and knowledge of the academic regarding the practice of dressings and management. In this regard, it is clear that the nurse must, as the owner of a clinic, act directly when it comes to management, so, to promote safety and well-being to the client with wounds, it is essential that this professional also maintains a good relationship with your team.